THOUGHTS OF ASY'ARIAN THEOLOGICAL FIGURES: QADHI ABU BAKR AL-BAQILLANI - Nasir, Muhammad; Ramadhani, Muhammad; Iqbal, Muhammad; Subban, Subban (Academy of Education Journal, 2023)
This century is famous for three mainstream schools in the history of Islamic thought, namely; first, the school of Islamic philosophers who only understand Islamic beliefs. Second, the Salafiyah school is very textual. Third, the Mu'tazilah school is a school that combines reason and naql while still making reason the determining factor when there are texts that conflict with the truths of reason (logic). Al-Asy'ari was originally one of the followers of the Mu'tazilah school until he was 40 years old. Furthermore, he formed formulas and patterns of thought that were different from the three schools of thought and he tried to combine the functions of both reason and texts while still providing guidelines that in fact reason must submit to texts